Factors Motivating the Public to Participate in Crowdsourcing of Crime Information - Solemon, Badariah; Abu Bakar, Wan Muhammad Luqman Wan (International Journal of Engineering and Technology, 2018)
This paper presents the results of an exploratory study conducted to identify the factors that influence people and communities to participate in crowdsourcing approach of crime information. The study uses as survey, self-administered questionnaires distributed to the crowd in the public areas in Selangor and Wilayah Persekutuan, Malaysia as well as through an online survey website. Analysis performed to more than half of 139 valid responses of the survey reveals that the respondents participated in crowdsourced crime reporting and sharing using recent technologies such as mobile application mainly to help reduce the crime rate (nature of problem factor); to contribute to the betterment of mankind and they like the idea of contributing to something of value to the world (altruism factor); to exchange ideas or knowledge on crime information with the crowdsourcing community and to obtain crime related information (learning factor); to share crime related information to others (interest in topic); and to alert others so they can be more cautious (reciprocity factor). Findings from this survey have guided a research work to develop a prototype of mobile application to demonstrate how the application can support neighborhood crime watch activity by enabling community members to share crime incidents information.